Evaluating the impact of conceptual change pedagogy on student attitudes and behaviors toward controversial topics in Iraq - Rea-Ramirez, Mary Anne; Abboud, Lena; Ramirez, Tina (Frontiers in Education, 2023)
This study assesses the effect of conceptual change pedagogy on students' attitudes toward pluralism and related rights within culturally sensitive contexts. Global efforts to address the spread of intolerant ideologies that foment radicalization, discrimination, and violence are fraught with controversy. Prior research on the Middle East and North Africa region has found that efforts to address these challenges in the field of education -including reform to curricula, the promotion of narratives inclusive of religious diversity, and civics education initiatives -have had varied levels of success. Absent from these efforts is the development of an effective pedagogy and the training of teachers to identify and address ideologies and behaviors that foment intolerance and conflict among students. Hardwired Global developed a teacher training program based on conceptual change theory and pedagogy to fill these needs. Conceptual change refers to the development of new ways of thinking and understanding of concepts, beliefs, and attitudes. Hardwired Global implemented the program in partnership with the regional Directorate of Education for Mosul and the Nineveh Plains region of Iraq from 2019-2023. From 2021-2023, Hardwired trained 485 teachers in 40 schools across the region. Following the training, teachers implemented two lessons. A mixed method research study -with a primary focus on quantitative data collected -was conducted to determine the effect of the program on student perceptions, understanding, and behavior towards key concepts inherent to pluralism. Quantitative data consisted of a pre-post survey with four multiple choice questions. Scores on pre-surveys were compared to post-surveys and a two sample paired t-test was applied. We documented statistically significant developments in students' conceptual understanding of key concepts inherent to pluralism and associated rights, including: respect for diversity in expression inclusion of diverse religious and/or ethnic communities, gender equality, and violent or non-violent approaches to conflict. Qualitative data consisted of semi-structured interviews with teachers and students implemented at the conclusion of the program and observations reported by Master Trainers and teachers during training and activity implementation. Findings suggest conceptual change pedagogy on pluralism and associated rights is a promising approach to education about controversial topics in conflict-affected and culturally sensitive environments.